High strength dual-crosslinked hydrogels with photo-switchable color changing behavior. (July 2019) - Wang, Beibei; Xiao, Xiaozhen; Zhang, Yuhuan; Liao, Liqiong
Graphical abstract: Highlights: Preparing a novel dual-crosslinked hydrogel with PEG and α-cyclodextrin. The as-prepared hydrogel possessed high tensile strength. The hydrogel exhibited real-time reversible photo-switchable color changing property. Providing a facile method for incorporating spiropyran into the hydrogel in aqueous. Abstract: Herein, high strength dual-crosslinked hydrogels with photo-switchable color changing behavior were designed and fabricated. In the mixture solution of α-cyclodextrin (α-CD), α-cyclodextrin-spiropyran (α-CD-SP), and poly(ethylene glycol) diacrylate (PEGDA), the PEGDA chains first threaded into the cavity of α-CD/α-CD-SP and form inclusion complexes to generate the physical gel; then, the as-prepared physical gels were subjected to photopolymerization to form a covalently crosslinked network. With the contribution of both no-covalent and covalent bond, the dual-crosslinked hydrogels possess high tensile strength, which is about fifteen times that of the pure PEG hydrogel. And due to the sacrifice of no-covalent bond, hydrogels showed high energy dissipation ratio, up to 75.3% and high fatigue resistance during loading-unloading tests. While the ingenious introduction of SP moieties, enables the as-prepared gels photo-switchable spatiotemporal color changing behavior reversibly. Erasable patterns on hydrogels could be written using UV light and erased by Vis light for multiple cycles. This flexible hydrogel with good physical performance shows high potential in photochromic flexible wearable devices.